Fabrication and properties of mullite ceramics from Ranong kaolin - Narumon Lertcumfu (2018)
© 2016 Trans Tech Publications, Switzerland. In the present study, mullite powders were prepared from fired Ranong kaolin powder at high temperatures. Differential thermal analyses and X-ray diffraction (XRD) technique were used to understand kaolin–mullite reaction sequence and phase formation of the starting material after a heat treatment, respectively. It was found that phase of mullite started to occure at ∼1000°C. Microstrural study by a scanning microscope, indicated that there was a change in microsture after the heat treatment, i.e. grain shape changed from equiaxed to needle grains shape. The AC conductivity decreased with decreasing the sintering temperature and 1500 °C ceramic presented a very high frequency stabilty of conductivity, suggesting that this martial can be used as an electrical insulator for wide frequency range.